The awareness of zakat income among UiTM Pahang staff / Muhammad Luqman Naim Kaharudin - Kaharudin, Muhammad Luqman Naim (2024)
The concept of al-mal al-mustafad states that zakat is required on any property received via business outcomes without any exchange process (buying and selling); in other words, it is obtained for its own purposes, such as salary, labour earnings, allowances, presents, and so on. The research aims are to analyse staff awareness, knowledge levels, and variables influencing involvement in zakat income at UiTM Pahang. The survey, which used a sample size of 111 employees, found a modest degree of knowledge and involvement in zakat income among university staff members. While most respondents recognise the significance of zakat income, there is a need for ongoing educational and awareness programmes to improve understanding and promote active involvement in this Islamic financial practice. Educational efforts, collaboration with Islamic institutions, policy integration, and community participation are all recommended as ways to develop a culture of generosity, social responsibility, and Islamic financial ethics within the university community. The study emphasises the need of continued education and community involvement in increasing understanding and participation in zakat income among university workers, paving the path for a better educated and involved community at UiTM Pahang.